A Systematic Review and Meta-Analysis on the Efficacy of Puerarin Injection as Adjunctive Therapy for Unstable Angina Pectoris - Shao, Huikai; Huang, Yang; Xu, Dongsheng; Huang, Shengfeng; Tong, Rongsheng (Frontiers in Cardiovascular Medicine, 2022)
Background: As an adjunctive therapy, puerarin injection has been widely applied for the treatment of Unstable Angina Pectoris (UAP) in China during the past decades. However, the efficacy of puerarin injection as adjunctive therapy for UAP has not been well confirmed. The purpose of this meta-analysis was to summarize the available evidence to estimate the efficacy of puerarin injection in treating UAP. Objective: A systematic review and meta-analysis with subgroup analysis and sensitivity analysis according to PRISMA principle were carried out to evaluate the efficacy of puerarin injection as adjunctive therapy in treating UAP. Methods: To obtain the published randomized controlled trials (RCTs) on puerarin injection, databases including China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database, Sino-Med, PubMed, China Science and Technology Journal Database (VIP), Medline, Google Scholar, Cochrane Library, Chinese Science Citation Database and Embase were systematically searched until June 2021. In this meta-analysis, Review Manager 5.3 and Stata 12.0 were employed to analyze the collected data. Based on the methodological quality, years of publications, sample size and dosages, sensitivity analysis and subgroup analysis were performed. Results: 17 RCTs involving 1459 patients were included in this meta-analysis. Results indicated that puerarin injection as adjunctive therapy was more superior than conventional Western medicine alone in reducing angina symptoms (RR = 1.22, 95%CI, 1.16 to 1.28, Z = 8.11, p < 0.00001) and improving ECG (RR = 1.32, 95%CI, 1.20 to 1.44, Z = 6.00, p < 0.00001), meanwhile reducing the frequency of angina attack (MD = -2.22, 95% CI -2.53 to -1.90, Z = 13.97, p < 0.00001) and the duration of angina attack (MD = -2.00, 95% CI -2.39 to -1.61, Z = 9.99, p < 0.00001) for the treatment of UAP. Results from the GRADE assessment suggested that the comprehensive quality of this evidence was low. Conclusions: This meta-analysis indicated that puerarin injection was more effective than using conventional Western medicine alone in the treatment of UAP. However, because of the low methodological quality of the included RCTs, more evidence was still needed to verify the efficacy of puerarin injection.